Lipids from Wastewater‐Activated Sludge Cultivated on Acetic Acid as Potential Alternatives to High‐Value Oils and Fats. (16th May 2019) - Fortela, Dhan Lord B.; Hernandez, Rafael; Revellame, Emmanuel; Holmes, William; Sharp, Wayne; Zappi, Mark
Abstract: This study focuses on new interpretations of the published literature by statistically evaluating the potential of microbial lipids from activated sludge (AS) as alternatives to high‐value oils and fats. There are two data analysis stages involved in this study after compilation and organization of fatty acid profiles from the literature databases: (1) comparison of fatty acid profiles of the cultivated AS lipids with that of oils and fats found in the literature databases, and (2) hierarchical cluster analysis of the fatty acids of the combined dataset of literature oils and fats, and the AS lipids. Results show that fatty acid profiles of lipids from cultivated AS were similar to the fatty acid profiles of some oils and fats of plant, animal, single‐microbial cultures, and algal origins; hence, lipids from AS could be potential alternatives to specialty oils and fats. The cultivation conditions of AS during lipid content enhancement may influence lipid application.